2009
DOI: 10.1016/j.ccr.2009.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Increased Radioresistance and Accelerated B Cell Lymphomas in Mice with Mdmx Mutations that Prevent Modifications by DNA-Damage-Activated Kinases

Abstract: Summary Mdmx is a critical negative regulator of the p53 pathway that is stoichiometrically limiting in some tissues. Post-translational modification and degradation of Mdmx after DNA damage have been proposed to be essential for p53 activation. We tested this model in vivo, where critical stoichiometric relationships are preserved. We generated an Mdmx mutant mouse in which three conserved serines (S341, S367, S402) targeted by DNA damage-activated kinases were replaced by alanines to investigate whether modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
86
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 65 publications
10
86
1
Order By: Relevance
“…This pathway was later confirmed by an elegant knock-in study in mice (32). Because both p21 and 14-3-3␥ bind to the extended central region of MDMX (26,29,33), we speculated that 14-3-3␥ might suppress MDMX-mediated p21 degradation by influencing the p21 binding to MDMX.…”
mentioning
confidence: 76%
“…This pathway was later confirmed by an elegant knock-in study in mice (32). Because both p21 and 14-3-3␥ bind to the extended central region of MDMX (26,29,33), we speculated that 14-3-3␥ might suppress MDMX-mediated p21 degradation by influencing the p21 binding to MDMX.…”
mentioning
confidence: 76%
“…In fact, no change in the stability of a temperature-sensitive mutant p53 was observed upon deletion of Mdm4 (Barboza et al 2008). Similarly, no noticeable difference in p53 ubiquitination pattern or p53 stability was observed in two other Mdm4 mutant mice, Mdm4DRING or MdmX-3SA (Wang et al 2009;Pant et al 2011). However, it is possible that the presence of Mdm2 masked the effect on p53 stability.…”
Section: Mdm4 An E4 Ligase?mentioning
confidence: 90%
“…To date, it has not been possible to genetically distinguish RING ligase activity from Mdm4 binding. Physiological disruption of the interaction between p53 and Mdm2/Mdm4 also occurs upon post-translational modifications and impacts p53 ubiquitination (Prives and Hall 1999;Ito et al 2002;Li et al 2002;Chao et al 2003Chao et al , 2006Xirodimas et al 2004;Wang et al 2009;Gannon et al 2012). Thus, the activity of the Mdm2 E3 ligase toward p53 is regulated by multiple parameters: the RING domain, the C terminus, and interactions with Mdm4.…”
Section: The Mdm2 E3 Ligasementioning
confidence: 99%
“…Previous studies of the impact of Mdm2 and Mdmx expression on p53 activity revealed that the p53 pathway is exquisitely sensitive to p53 protein levels and basal activity, which can be modulated by p53-negative regulators (Mendrysa et al 2003;Terzian et al 2007;Wang et al 2009). Since Mdm2 heterozygous mice are known to have elevated p53 activity (Terzian et al 2007), we compared their radiosensitivity with p53 7KR mice.…”
Section: Krmentioning
confidence: 99%